Attacking stressed Pseudomonas protegen biofilms with Wi-Fi - Najmah Abdul Razak (2017)
Pseudomonas protegens (Pf-5) is a plant-based, gram-negative bacteria that can be readily found in various surrounding environments; from the natural-occurring environments to the man-made industrial environments. Inoculums were diluted at an absorbance of 0.05 to obtain measurements of 1×108 CFU/ml at a wavelength of 670 nm. The biofilms of the Pseudomonas protegens were cultured in 96-polystyrene microplates at 25±0.1°C with an agitation of 100 rpm in M9 minimal media at 10 varying concentrations of MgCl2 (0 Mm/L, 0.0145 Mm/L, 0.0291 Mm/L, 0.058 Mm/L, 0.116 Mm/L, 0.23 Mm/L, 0.465 Mm/L, 0.93 Mm/L, 2 Mm/L and 3.72 mM/L).